Inclusion of an Exoneration Clause in a Standard Agreement on the Transfer of Liability on the Terms of Use of Gocar - Eryna Dian Osada; Eny Sulistyowati (Universitas Negeri Surabaya, 2025)
Standard agreements often contain standard clauses which, if not properly regulated, can lead to an imbalance between business actors and consumers. Article 18 of the Consumer Protection Law (GCPL) prohibits business actors from including clauses that transfer responsibility to consumers. However, GoCar’s terms of use, particularly point 2E, contain an exoneration clause that contradicts Article 18 paragraph (1) letter a of the GCPL. This study aims to analyze the compatibility of GoCar’s terms of use with the principles of consumer protection, and to assess the proper form of liability that Gojek should bear in the event of consumer losses related to safety during service use. The research adopts a normative legal method with statutory and conceptual approaches. The findings reveal that GoCar’s terms are inconsistent with the principles of justice, safety, and consumer security as mandated in Article 2 of the GCPL. Furthermore, business actors such as Gojek are liable under Article 19 of the GCPL, which provides for compensation through refunds, healthcare, or other restitution. This liability is subject to proof of fault, and the burden of such proof lies with the business actor, as stated in Articles 19(5), 22, and 28. The study recommends that Gojek revise its terms of use to align with consumer protection principles and avoid unfair clauses that may harm consumers.